2020
DOI: 10.1002/app.50167
|View full text |Cite
|
Sign up to set email alerts
|

Soluble network polymers based on trifluoropropyl‐substituted open‐cage silsesquioxane: Synthesis, properties, and application for surface modifiers

Abstract: Fluorinated completely condensed polyhedral oligomeric silsesquioxanes (F-CC-POSSs) are widely utilized as surface modifiers for polymeric materials because of their polyhedral and fluorine-rich structures, which generate polymers with lower surface energies under molecular-level control. In contrast, their derivatives, fluorinated incompletely condensed or open-cage POSSs (F-IC-POSSs), have similarly intriguing structures, but their utilization for polymer synthesis remains undeveloped. Herein, fluorinated ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Silsesquioxanes [RSiO 1.5 ] n are popular building blocks for generating a variety of new molecules and functional materials. Their examples include three-dimensional emulsifiers, surface modifiers, nanofillers, hydrogen-bonding catalysts, atomic oxygen resistant composite films, and monomers for copolymerization . Another important feature of partly condensed silsesquioxanes is an ability to serve as ligands for various cage metalladerivatives. The vast structural variety of cagelike metallasilsesquioxanes (CLMSs) endows them with a bunch of practically important properties, e.g., photophysical or magnetic, , including single molecule magnets and spin glasses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silsesquioxanes [RSiO 1.5 ] n are popular building blocks for generating a variety of new molecules and functional materials. Their examples include three-dimensional emulsifiers, surface modifiers, nanofillers, hydrogen-bonding catalysts, atomic oxygen resistant composite films, and monomers for copolymerization . Another important feature of partly condensed silsesquioxanes is an ability to serve as ligands for various cage metalladerivatives. The vast structural variety of cagelike metallasilsesquioxanes (CLMSs) endows them with a bunch of practically important properties, e.g., photophysical or magnetic, , including single molecule magnets and spin glasses .…”
Section: Introductionmentioning
confidence: 99%
“…Silsesquioxanes [RSiO 1.5 ] n are popular building blocks for generating a variety of new molecules and functional materials. 1−7 Their examples include three-dimensional emulsifiers, 8 surface modifiers, 9 nanofillers, 10 hydrogen-bonding catalysts, 11 atomic oxygen resistant composite films, 12 and monomers for copolymerization. 13 Another important feature of partly condensed silsesquioxanes is an ability to serve as ligands 14 for various cage metalladerivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our experiments, we used commercially available platinum catalysts: Karstedt's catalyst (Pt 2 (dvs) 3 (I), PtO 2 /XPhos (XPhos = 2-dicyclohexylphosphino-2′,4′,6′-tri-(iso-propyl)biphenyl) (II), and Pt(PPh 3 ) 4 (III)) (Table 1, entries 1−6). The reactions were carried out with reagents in a ratio [1]: [2] = 1:3, in toluene or tetrahydrofuran (THF), at 100 °C, without any purification of the acquired chemicals. The progress of the reactions was monitored by 1 H NMR after 24 h, while the process selectivity was calculated using 1 H and 29 Si NMR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Trifunctional incompletely condensed silsesquioxanes (RSiMe 2 O) 3 R′ 7 Si 7 O 9 ( IC-POSS s) have attracted much attention since they were first recognized as building nanoblocks for the synthesis of advanced hybrid materials. These compounds, based on the silicon–oxygen cubic core in which one corner is open, inherit many features of completely condensed polyhedral oligomeric silsesquioxanes (R 8 Si 8 O 12 , POSS) and at the same time possess unique properties that can give them an advantage over the POSS in some areas of application. For instance, it was found that open-cage structures IC-POSS s are characterized by excellent thermal stability, similar to their POSS analogues.…”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of 3,7,14-tris(dimethylsilylsiloxy)hepta(3,3,3trifluoropropyl)tricycloheptasiloxane (TFP-H) and 3,7,14-tris-( d i m e t h y l v i n y l s i l y l s i l o x y ) h e p t a ( 3 , 3 , 3 -t r ifl u o r o p r o p y l )tricycloheptasiloxane (TFP-V) were prepared according to a previous report. 43 3,7,14-Tris(dimethylallylsilylsiloxy)hepta(3,3,3trifluoropropyl)tricycloheptasiloxane (TFP-A) was synthesized ac-cording to the method for TFP-V in 72% yield. 1 29 Si-NMR (in CDCl 3 , 80 MHz): δ 9.0, −1.8, −66.2, −68.2, −69.5 ppm.…”
Section: ■ Introductionmentioning
confidence: 99%